Closed Kinetic Chain Exercise efektif Dalam Meningkatkan Kemampuan Fungsional Pada Osteoartritis Lutut - Faizah Abdullah Djawas; Wafa Rahmalillah Isna (LPPM Universitas Abdurrab, 2020)
Background: Osteoarthritis (OA) of the knee is a chronic joint disease that is characterized by abnormalities in the cartilage which will result in bones rubbing against each other, abrasion of joint cartilage and formation of osteophytes on the surface of the joints that cause symptoms such as stiffness, pain, and limitation of movement to the knee joint. Closed kinetic chain exercise (CKCE) exercise therapy generally provides benefits in reducing complaints that are expected to improve the patient's functional ability to perform activities optimally. The purpose of this study is to determine the effectiveness of closed kinetic chain exercise (CKCE) exercise methods in cases of knee osteoarthritis. Methods: A single case study, providing physiotherapy interventions for a 72-year-old woman with a diagnosis of knee OA. CKCE in the form of mini squatt movements, QSE, and step up and step down is given for 2 weeks with 4 evaluations. Pain intensity assessment using VAS, joint range of motion (ROM) assessment using goniometer, muscle strength assessment using MMT, and to assess patient functional development were measured using WOMAC parameters. Results: There was a decrease in the value of motion pain VAS at the end of the therapy session from VAS 3 to VAS 1, a decrease in pressure pain VAS value from VAS 2 to VAS 1, there was an increase in knee flexion ROM 1200 to 1250, there was an increase in MMT from 4 to 5 which was associated with WOMAC score from 37 to 26, which shows that there is an increase in the patient's functional ability by 20% Conclusion: This study shows that the closed kinetic chain exercise (CKCE) exercise therapy method can improve functional ability in knee osteoarthritis as measured using WOMAC parameters.